The role of atria in ventricular fibrillation after continuous-flow left ventricular assist device implantation in ovine model - Yu, Xin-Yi; Shi, Jian-Wei; Rong, Yan-Sheng; Chen, Yuan-Lu; Liu, Tian-Wen; Zang, Yi-Rui; Fu, Ze-An; Zhang, Jie-Min; Han, Zhi-Fu; Liu, Zhi-Gang (Frontiers in Cardiovascular Medicine, 2023)
Objectives This study attempted to explore the hemodynamics and potential mechanisms driving pulmonary circulation in status of ventricular fibrillation (VF) following continuous-flow left ventricular assist device (CF-LVAD) implantation. Methods An ovine CF-LVAD model was built in small-tailed Han sheep, with the pump speed set as 2,400 rpm. VF was induced following ventricular tachycardia using a temporary pacemaker probe to stimulate the right and left ventricular free walls. The central venous pressure (CVP), pump flow (PF), pulmonary artery flow (PAF) and other major indicators were observed and recorded after VF. Results Low-flow systemic and pulmonary circulation could be sustained for 60 min under VF with sinus atrial rhythm after CF-LVAD implantation. The CVP gradually increased. The mean PF declined from 1.80 to 1.20 L/min, and the mean PAF decreased from 1.62 L/min to 0.87 L/min. Under VF with atrial fibrillation, the systemic and pulmonary circulation couldn’t be sustained. The CVP jumped from the 5 mmHg baseline to 12 mmHg, the mean PF rapidly decreased from 3.45 L/min to 0.79 L/min, and the PAF declined from 3.94 L/min to 0.77 L/min. Conclusion The atrial rhythm and function might be essential for the circulation maintenance in patients with VF after CF-LVAD implantation.